Design of new hypervalent iodine azidating reagents: synthesis and properties - Mironova I. A. Irina Andreevna; Kirsch S. F.; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Zhdankin V. V. Viktor Vladimirovich (2021, 2021)
Title screen